Modifikasi Kotak Polistiren Untuk Penyimpanan Dingin Sayur Kubis Dengan Menggunakan Es Kering Sebagai Media Pendingin - Bagus Made Brahmanda Diputra; Ida Bagus Putu Gunadnya; I Putu Gede Budisanjaya (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2021)
Research had been carried out to modify polystyrene box as fresh cabbage delivery box using dry ice as a cooling medium. The research aims were to find out the most suitable model box to maintain the freshness of the vegetables. Modified polystyrene box was made by separating the box into two compartments, one compartment for placing dry ice, and another compartment for storing the fresh cabbage. The box was modified into five types which consisted of two types of the box where the cooling medium was placed below the fresh vegetable, while for the rest, the cooling medium was placed above the vegetable. The tests were performed for 7 hours with the hourly observation that consisted of the temperature surrounding the model box, temperature inside the box, and temperature of the center of the fresh cabbage. Other conducted measurements were the weight of dry ice used during cold storage, weight loss of fresh cabbage, visual observation on the deterioration of the fresh cabbage, and energy equilibrium calculation. Placing dry ice below the fresh cabbage caused the center temperature of the fresh cabbage to far above the recommended storing temperature, 0oC, while placing the cooling medium above the vegetable gave a negative impact on the vegetable where the center temperature of the fresh cabbage was below 0oC for the two types of model boxes, except for the fifth type box where dry ice was placed in a basin made of zink plate. Based on energy calculation it was revealed that almost more than 75% of cooling energy was used to overcome the surrounding cooling load. It was found that the most suitable model box for storing the fresh cabbage was the fifth type.